2015
DOI: 10.1016/j.celrep.2015.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Association of Pre-stored Information to Generate a Qualitatively New Memory

Abstract: Memory is thought to be stored in the brain as an ensemble of cells activated during learning. Although optical stimulation of a cell ensemble triggers the retrieval of the corresponding memory, it is unclear how the association of information occurs at the cell ensemble level. Using optogenetic stimulation without any sensory input in mice, we found that an artificial association between stored, non-related contextual, and fear information was generated through the synchronous activation of distinct cell ense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(122 citation statements)
references
References 35 publications
4
116
2
Order By: Relevance
“…Remarkably, mice did not learn to fear this second context but now froze when placed back in the original context that had never been paired with shock, indicating that the experimentally reinstated memory had been conditioned and a 'false' memory had been created. Taking this strategy one step further, another group of researchers successfully cre ated a false association between two distinct engrams in mice 137 . Hippocampal CA1 neuronal ensembles that were active while the animal was in a neutral context (that is, a context not paired with shock) were labelled.…”
Section: Criteria Satisfied By Artificial Expression Studiesmentioning
confidence: 98%
“…Remarkably, mice did not learn to fear this second context but now froze when placed back in the original context that had never been paired with shock, indicating that the experimentally reinstated memory had been conditioned and a 'false' memory had been created. Taking this strategy one step further, another group of researchers successfully cre ated a false association between two distinct engrams in mice 137 . Hippocampal CA1 neuronal ensembles that were active while the animal was in a neutral context (that is, a context not paired with shock) were labelled.…”
Section: Criteria Satisfied By Artificial Expression Studiesmentioning
confidence: 98%
“…In fact, a recent report using optogenetic technology showed that this is conceivable. Ohkawa et al (2015) demonstrated that independent contextual and aversive information can become integrated into a single NMDA and protein synthesis-dependent mnemonic trace. This integrated new memory seems to be formed through coactivation of both traces, in a hebbian-like mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…We argue, however, that these experiments provide evidence for how the hippocampus can work and not necessarily for how it does work. While minutes-long stimulation of a fraction of cells at 5 Hz in the retrosplenial cortex (Cowansage et al, 2014), 20 Hz in the DG (Liu et al, 2012; Ramirez et al, 2013; Redondo et al, 2014; Ohkawa et al, 2015; Ryan et al, 2015; Roy et al, 2016; Stefanelli et al, 2016) and 20 Hz in the basolateral amygdala or ventral CA1 (Yiu et al, 2014; Gore et al, 2015a; Okuyama et al, 2016; Rashid et al, 2016) does not recapitulate endogenous physiological firing patterns, we believe that these findings yield powerful strategies for artificially commandeering mnemonic processes and for navigating memory’s largely unexplored capacity to be externally controlled (for reasons discussed below). Notably, recent work has demonstrated that the DG increases in beta amplitude (15–30 Hz) in an associative learning task, perhaps reflecting an oscillatory shift in processing states that 20 Hz DG stimulations partly capture and/or recapitulate (Rangel et al, 2015).…”
Section: The Many Ways To Start a Carmentioning
confidence: 99%
“…For example, Ohkawa et al (2015) successfully utilized a 20 Hz stimulation protocol in CA1 to link a context-specific, hippocampus-mediated memory with unconditioned stimulus-responsive cells in the basolateral amygdala, thus leading to the formation of an artificial associative memory. It is noteworthy that Ohkawa et al (2015) tagged ~13% of CA1 cells with a lentivirus ChR2 vector, whereas Ramirez et al (2013) tagged ~50% of CA1 cells with an AAV9 ChR2 vector; we speculate that the spatial specificity of labeling a smaller proportion of cells with the former strategy managed to capture more “signal” in terms of CA1 context specific cells whereas tagging ~50% of cells in the latter case perhaps captured more “noise” during the labeling period and thus failed to unmask a behavioral response. Therefore, a boundary condition for achieving context-specific reactivation in CA1 appears to be both frequency of stimulation and number of cells tagged.…”
Section: The Many Ways To Start a Carmentioning
confidence: 99%